Benzo[de]naphtho[1,8-gh]quinolines: synthesis, photophysical studies and nitro explosives detection - Igor L. Nikonov; Igor A. Khalymbadzha; Leila К. Sadieva; Maria I. Savchuk; Ekaterina S. Starnovskaya; Dmitry S. Kopchuk; Igor S. Коvalev; Grigory А. Kim; Oleg N. Chupakhin (Chimica Techno Acta)
A rational synthetic approach to substituted naphtho[1,8-gh]quinolines using intramolecular cyclization in the presence of potassium in the series of (naphthalen-1-yl)isoquinolines is described. The photophysical properties of the obtained compounds were studied; in particular, fluorescence emission was detected in the range 454 - 482 nm with a quantum yield of up to 54%. We also calculated the HOMO-LUMO energies and optimized molecular structures for the resulting fluorophores. Based on the results of fluorescence titration, the Stern-Volmer constants (up to 21587 M-1) and the detection limits of nitroanalytes (up to 1.4 ppm) were calculated, confirming the possibility of their use as potential chemosensors for the visual detection of nitro-containing explosives.